The path to eradication: a progress report on the malaria-eliminating countries. Issue 10029 (23rd April 2016) - Newby, Gretchen; Bennett, Adam; Larson, Erika; Cotter, Chris; Shretta, Rima; Phillips, Allison A; Feachem, Richard G A
Summary: In the past several years, as worldwide morbidity and mortality due to malaria have continued to decrease, the global malaria community has grown increasingly supportive of the idea of malaria eradication. In 2015, three noteworthy global documents were released—the WHO's Global Technical Strategy for Malaria 2016–2030, the Roll Back Malaria Partnership's Action and Investment to defeat Malaria 2016–2030, and From Aspiration to Action: What Will It Take to End Malaria?—that collectively advocate for malaria elimination and eradication and outline key operational, technical, and financial strategies to achieve progress toward malaria eradication. In light of this remarkable change in global attitudes toward malaria elimination and eradication, and as the malaria community debates how and when to embark on this ambitious goal, it is important to assess current progress along the path to eradication. Although low-income, high-burden countries are often the focus when discussing the substantial challenges of eradication, the progress toward elimination in middle-income, low-burden countries is a major driver of global progress and deserves better recognition. Additionally, although global support and guidance is essential for success, malaria elimination and eradication efforts will ultimately be driven at the country level and achieved in a collaborative manner, region by region. In this Review, we examine the present status of the 35 malaria-eliminating countries, summarise existing national and regional elimination goals and the regional frameworks that support them, and identify the most crucial enabling factors and potential barriers to achieving eradication by a theoretical end date of 2040.